2014
DOI: 10.1111/anae.12546
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of analgesic efficacy of four‐quadrant transversus abdominis plane (TAP) block and continuous posterior TAP analgesia with epidural analgesia in patients undergoing laparoscopic colorectal surgery: an open‐label, randomised, non‐inferiority trial

Abstract: SummaryPosterior transversus abdominis plane blocks have been reported to be an effective method of providing analgesia after lower abdominal surgery. We compared the efficacy of a novel technique of providing continuous transversus abdominis plane analgesia with epidural analgesia in patients on an enhanced recovery programme following laparoscopic colorectal surgery. A non-inferiority comparison was used. Adult patients undergoing elective laparoscopic colorectal surgery were randomly assigned to receive con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
128
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(134 citation statements)
references
References 19 publications
3
128
0
3
Order By: Relevance
“…Future studies investigating postoperative analgesia following laparoscopic appendicectomy should focus on TAP techniques that provide a greater area of abdominal wall analgesia (30,31) or on analgesic therapies targeted toward the visceral pain component. The benefits of TAP block for laparoscopic abdominal procedures appear to be less that of the corresponding open surgical procedures, (21,24,(32)(33)(34) and presently, the role of this regional anaesthetic procedure for lower abdominal laparoscopic surgery requires further evaluation with larger clinical trials, both to determine the most effective TAP technique and to investigate more precisely its benefits in terms of surgical recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies investigating postoperative analgesia following laparoscopic appendicectomy should focus on TAP techniques that provide a greater area of abdominal wall analgesia (30,31) or on analgesic therapies targeted toward the visceral pain component. The benefits of TAP block for laparoscopic abdominal procedures appear to be less that of the corresponding open surgical procedures, (21,24,(32)(33)(34) and presently, the role of this regional anaesthetic procedure for lower abdominal laparoscopic surgery requires further evaluation with larger clinical trials, both to determine the most effective TAP technique and to investigate more precisely its benefits in terms of surgical recovery.…”
Section: Discussionmentioning
confidence: 99%
“…One study found that, after laparoscopic colorectal surgery, a four-quadrant TAP block with continuous infusion via bilateral posterior TAP catheters (0.365% levobupivacaine 2.5 mgÁkg postoperatively). 35 In contrast, a systematic review and meta-analysis on Cesarean delivery found that TAP block alone was less effective than intrathecal morphine in managing pain at 24 hr (mean difference [MD] 0.98; 95% CI 0.06 to 1.91) and resulted in greater 24-hr morphine consumption (MD 8.42 mg; 95% CI 1.74 to 15.10), while the former was associated with an increased incidence of side effects such as sedation and PONV. 36 There are generally few risks associated with TAP block, including intraperitoneal injection of local anesthetic (\ 2%) as well as a few case reports of transient femoral nerve palsy and bowel hematoma.…”
Section: Regional Techniquesmentioning
confidence: 99%
“…Morphine delays the recovery of bowel function and slows the functional recovery. Epidural analgesia has no long recommended in laparoscopic surgery therefore in order to reduce postoperative morphine consumption the use of NSAIDs has been advocated as part of multimodal analgesia [87,88]. However, some concerns are raised because some experimental studies have stressed the risk of a higher incidence of anastomotic leakages especially ileum dehiscence, with the use of NSAIDs in postoperative period [89].…”
Section: Postoperative Effects After Abdominal Surgerymentioning
confidence: 99%